2007
DOI: 10.1210/jc.2006-1748
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Thyroid Dysfunction in Early Pregnancy: Universal Screening or Targeted High-Risk Case Finding?

Abstract: Targeted thyroid function testing of only the high-risk group would miss about one third of pregnant women with overt/subclinical hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
251
2
26

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(316 citation statements)
references
References 19 publications
25
251
2
26
Order By: Relevance
“…We did not find any correlation between hypothyroxinaemia and TPOAb in this study, which was consistent with the results from the study of Vaidya [16]. Iodine deficiency might be one of the main causes of hypothyroxinaemia [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not find any correlation between hypothyroxinaemia and TPOAb in this study, which was consistent with the results from the study of Vaidya [16]. Iodine deficiency might be one of the main causes of hypothyroxinaemia [21].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies had reported the prevalence of hypothyroidism during pregnancy [14][15][16]. However, reference intervals obtained from non-pregnant women were used as the criteria in most studies, which might cause a high percentage of potential misclassification of thyroid hormone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Normal thyroid hormone levels promote normal growth and development in the fetus and prematurely born neonates. [7][8][9][10][11] The data provided in this article are taken from a randomized, double-blind clinical trial, which examined whether increased intravenous amino-acid supplementation would improve growth. In this trial, it was hypothesized that increased amino-acid supplementation would improve growth and well being and that normalization of serum amino acids would increase thyroxine levels.…”
Section: Introductionmentioning
confidence: 99%
“…Дефіцит тиреоїдних гормонів у другій по-ловині вагітності та в ранні терміни неонатального періоду призводить до порушень процесів мієлініза-ції. В подальшому ці гормони беруть участь у фор-муванні механізмів адаптації, впливають на ріст і фізичний розвиток дитини [7,8]. Під час вагітності на організм жінки має вплив низка специфічних для цього стану чинників, які можуть призвести до зна-чної стимуляції ЩЗ [9,10].…”
Section: вступunclassified
“…У регіонах йодної ендемії особливого значення набуває проблема виношування вагітності на тлі патології ЩЗ, яка виявляється у 18,2 % випадків за-грози переривання вагітності [7]. Тиреоїдний статус суттєво відображається як на перебігу вагітності, ха-рактері пологової діяльності, лактації, так і на розви-тку плода та новонародженого, відіграючи важливу роль у забезпеченні інтелектуального, фізичного та статевого розвитку дитини [2,11].…”
Section: обговоренняunclassified